Disease and the environment in the medieval and early modern worlds
1 online resource (xv, 212 pages)
Keywords: "This volume brings together environmental and human perspectives, engages with both historians and scientists, and, being mindful that environments and disease recognise no boundaries, includes studies that touch on Europe, the wider Eastern Mediterranean world, Asia, Africa, and the Americas. Lori Jones is a medical historian at Carleton University and the University of Ottawa, Canada. Her research focuses primarily on plague texts and images. She is the author of Patterns of Plague (2022) and co-editor of Death and Disease in the Medieval and Early Modern World (2022)"--